Basic issues for a new GATT round - Hajo Hasenpflug (Intereconomics, 1972)
The most extensive tariff cuts in the history of GATT were completed with the fifth and final stage of the Kennedy Round. Tariffs on a volume of trade in excess of 40 bn have been reduced by an average of 50 p.c.
Keywords: 330; Trade And Development